ANALISIS PENYUSUNAN LAPORAN PPh PASAL 21 MENGGUNAKAN E-SPT PADA PT SENTUL CITY - Yopy Ratna Dewanti; Naufal Hanif Adani; Utep Sobali; Edison Parlindungan (DIVERSITY: Journal of Multi Science Linearity, 2024)
This Final Assignment Report is entitled "Analysis of the Preparation of Income Tax Article 21 using e-SPT at PT. Sentul City Tbk. The purpose of this study is to determine how the calculation, deduction, deposit, reporting and accounting recording of Income Tax Article (PPh) 21 at PT. Sentul City Tbk. The methods used in this study are observation data, interview data, library data, tracing, and using qualitative descriptive methods. Income Tax Article 21 is a tax imposed on income in the form of salaries, honorarium wages, allowances, and other payments under any name in connection with work, services, or activities carried out by domestic Individual Taxpayers. The results of this study are the Calculation of Income Tax (PPh) Article 21 at PT. Sentul City Tbk in 2024 is carried out using the gross or gross-up method according to company policy, and considering the components of fixed and non-fixed income, deductions such as pension contributions, and the PTKP (Non-Taxable Income) status of each employee, Deposit of Income Tax Article 21 is carried out by PT. Sentul City Tbk on time using e-Billing Reporting of Article 21 Income Tax is done electronically using e-Filing or e-SPT by attaching proof of deduction. Accounting recording of Article 21 Income Tax at PT. Sentul City Tbk is carried out by following applicable financial accounting standards and the principles of transparency and accountability.